Challenging the top player: a preliminary study on testosterone response to an official chess tournament - Mendoza Torrico, Guillermo; Jimenez Lopez, Manuel; García-Romero, Jerónimo; Garcia Bastida, Jorge; Rivilla, Iván; Carrillo-de-Albornoz, Margarita; Barón-López, Francisco Javier; Benítez-Porres, Javier; Alvero-Cruz, José Ramón (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
According to the Challenge Hypothesis, high levels of testosterone (T) are associated with status-seeking behaviors, especially in competitive situations. However, there have not been many studies about rivals’ social status and pre-competition neuroendocrine responses. The aim of this study was to analyze whether the participants in a chess tournament showed different pre-match testosterone and cortisol levels depending on differences in ELO (i.e., the International Chess Federation rating to rank the competitive potential and social status between players). The sample was six male participants (mean ± SD) aged 25.5 ± 8.4 years with experience in official tournaments of 16.33 ± 5.72 years and an average ELO rating of 2217.67 ± 112.67. Saliva samples were collected before each round for hormonal determination when participants competed against a rival with a different ELO rating. After five competition rounds per participant, higher rival pre-competition T concentrations were shown when playing against the best-rated participant, but there were no differences in cortisol (C). The multilevel model confirmed rises in rivals’ precompetitive T levels modulated by the difference in the opponent´s ELO rating. No significant changes were observed in C. The results suggest that the rival´s status can determine the opponent´s anticipatory neuroendocrine responses to an official chess tournament. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Testosterona; Adolescent; Adult; Competitive behavior; Humans; Hydrocortisone; Male; Recreation; Saliva; Testosterone; Young adult